2017
DOI: 10.1111/head.13073
|View full text |Cite
|
Sign up to set email alerts
|

Post Hoc Subanalysis of Two Randomized, Controlled Phase 3 Trials Evaluating Diclofenac Potassium for Oral Solution: Impact of Migraine‐Associated Nausea and Prior Triptan Use on Efficacy

Abstract: ObjectiveTo determine whether baseline nausea or prior triptan treatment for migraine impact the effectiveness of diclofenac potassium for oral solution in treating acute migraine.BackgroundA great deal of variability exists in patients' response to migraine medications. Migraine‐associated nausea is common and debilitating and can reduce the effectiveness of oral medications. It may cause patients to delay taking oral medications, which is known to diminish therapeutic outcomes, or to avoid taking them altoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, treatment‐by‐subgroup interaction p values from the logistic regression model, which accounts for all data, found that this pattern was not significant for any of the efficacy outcome measures evaluated. Increased placebo responses in treatment‐naïve participants have been observed in other clinical trials of acute treatment of migraine 22–24 and, although the reasons for this consistent finding are unclear, they may be attributable to a number of factors. It is possible that the diagnosis of migraine was less robustly established in these triptan‐naïve participants and, therefore, this did not lead to prior prescription of a standard migraine‐specific treatment, or that expectation of a new treatment in those who have not had migraine‐specific treatments amplifies the placebo response.…”
Section: Discussionmentioning
confidence: 66%
“…However, treatment‐by‐subgroup interaction p values from the logistic regression model, which accounts for all data, found that this pattern was not significant for any of the efficacy outcome measures evaluated. Increased placebo responses in treatment‐naïve participants have been observed in other clinical trials of acute treatment of migraine 22–24 and, although the reasons for this consistent finding are unclear, they may be attributable to a number of factors. It is possible that the diagnosis of migraine was less robustly established in these triptan‐naïve participants and, therefore, this did not lead to prior prescription of a standard migraine‐specific treatment, or that expectation of a new treatment in those who have not had migraine‐specific treatments amplifies the placebo response.…”
Section: Discussionmentioning
confidence: 66%
“…35 Triptans may also cause neurological side effects and a low but increased risk for cardiovascular events. 36,37 Further, 30%-40% of patients 38 experience inadequate pain relief and fail to achieve pain-free status with triptans and may have an increased risk of medication-overuse headache. 39,40 While ergot alkaloids, specifically DHE (first approved in 1946), have been available for decades to treat acute migraine and offer an alternative to triptans, use of existing IV, subcutaneous (SC), intramuscular (IM), and nasal formulations of DHE is limited by patient concerns about ease of use and consistency of response, in addition to safety/tolerability concerns from both patients and health care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Triptans are the standard of care for treating acute episodic migraine, but their oral administration is often hampered by the nausea and vomiting that can accompany migraine . Triptans may also cause neurological side effects and a low but increased risk for cardiovascular events . Further, 30%–40% of patients experience inadequate pain relief and fail to achieve pain‐free status with triptans and may have an increased risk of medication‐overuse headache .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, acute treatment can be essential in the management of nausea associated with migraine. NSAIDs could be effective in alleviating nausea in patients who have not taken any triptans [ 72 ] and there is a recent meta-analysis that supports gepants as an effective treatment for nausea in patients with episodic migraine [ 73 ]. Special attention must be paid to patients consuming opioids.…”
Section: Nausea and Vomitingmentioning
confidence: 99%